Advancements in non-dopaminergic treatments for schizophrenia: a systematic review of pipeline developments - Komatsu, Yuki; Takehara, Moe; Hart, Xenia Marlene; Takahashi, Yuna; Hori, Satoko; Ueno, Fumihiko; Uchida, Hiroyuki (Pharmacopsychiatry, 2024)
INTRODUCTION: Conventional antipsychotic drugs that attenuate dopaminergic neural transmission are ineffective in approximately one-third of patients with schizophrenia. This necessitates the development of non-dopaminergic agents. - METHODS: A systematic search was conducted for completed phase II and III trials of compounds for schizophrenia treatment using the US Clinical Trials Registry and the EU Clinical Trials Register. Compounds demonstrating significant superiority over placebo in the primary outcome measure in the latest phase II and III trials were identified. Collateral information on the included compounds was gathered through manual searches in PubMed and press releases. - RESULTS: Sixteen compounds were identified; four compounds (ulotaront, xanomeline/trospium chloride, vabicaserin, and roluperidone) were investigated as monotherapy and the remaining 12 (pimavanserin, bitopertin, BI 425809, encenicline, tropisetron, pregnenolone, D-serine, estradiol, tolcapone, valacyclovir, cannabidiol, and rimonabant) were examined as add-on therapy. Compared to the placebo, ulotaront, xanomeline/trospium chloride, vabicaserin, bitopertin, estradiol, cannabidiol, rimonabant, and D-serine showed efficacy for positive symptoms; roluperidone and pimavanserin were effective for negative symptoms; and encenicline, tropisetron, pregnenolone, tolcapone, BI 425809, and valacyclovir improved cognitive function. - DISCUSSION: Compounds that function differently from existing antipsychotics may offer novel symptom-specific therapeutic strategies for patients with schizophrenia.